2015
DOI: 10.1002/2014wr016539
|View full text |Cite
|
Sign up to set email alerts
|

Chute cutoff as a morphological response to stream reconstruction: The possible role of backwater

Abstract: Stream restoration efforts often aim at creating new unconstrained meandering channels without weirs and bank revetments. In reconstructed streams, the initial morphological response of the new streams is often rapid, until a dynamic equilibrium is reached. Here we report on a chute cutoff that occurred within 3 months after realization of a stream restoration project, caused by a plug bar that formed in response to a backwater effect. The temporal evolution of the morphology of both the new and the old channe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…Over shorter time scales, cutoffs act as "shot" perturbations [Camporeale et al, 2008] to river morphodynamics by increasing the bed slope and stream power both upstream and downstream [Biedenharn et al, 2000;Hooke, 2004;Jugaru Tiron et al, 2009], injecting downstream pulses of sediment excavated from the floodplain during chute channel formation [Fuller et al, 2003;Zinger et al, 2011], and substantially altering the local channel planform and hydrodynamics [Hooke, 2004;Zinger et al, 2013]. Considerable attention has been given to local cutoff-induced channel response immediately adjacent to and within cutoffs [Hooke, 1995;Fuller et al, 2003;Zinger et al, 2011Zinger et al, , 2013 as well as factors controlling their occurrence [Grenfell et al, 2014;Eekhout and Hoitink, 2015;Słowik, 2016]. However, the spatial and temporal extents to which cutoff perturbations induce nonlocal morphologic change remain unknown, largely due to difficulties of observing morphodynamics over sufficiently large spatial scales and high temporal frequencies to capture changes [Winkley, 1977;Hooke, 1995].…”
Section: Introductionmentioning
confidence: 99%
“…Over shorter time scales, cutoffs act as "shot" perturbations [Camporeale et al, 2008] to river morphodynamics by increasing the bed slope and stream power both upstream and downstream [Biedenharn et al, 2000;Hooke, 2004;Jugaru Tiron et al, 2009], injecting downstream pulses of sediment excavated from the floodplain during chute channel formation [Fuller et al, 2003;Zinger et al, 2011], and substantially altering the local channel planform and hydrodynamics [Hooke, 2004;Zinger et al, 2013]. Considerable attention has been given to local cutoff-induced channel response immediately adjacent to and within cutoffs [Hooke, 1995;Fuller et al, 2003;Zinger et al, 2011Zinger et al, , 2013 as well as factors controlling their occurrence [Grenfell et al, 2014;Eekhout and Hoitink, 2015;Słowik, 2016]. However, the spatial and temporal extents to which cutoff perturbations induce nonlocal morphologic change remain unknown, largely due to difficulties of observing morphodynamics over sufficiently large spatial scales and high temporal frequencies to capture changes [Winkley, 1977;Hooke, 1995].…”
Section: Introductionmentioning
confidence: 99%
“…Other authors have reported significant effects on chute cutoff mechanisms. Constantine et al (2010) consider that flood events influence floodplain overflow and erosion and Eekhout and Hoitink (2015) indicate that in-channel changes affect hydraulic flow and channel sedimentation. Hooke (1995) describes cutoff adjustments in the English Dane and Bollin rivers with rapid sediment accumulation in the cutoff entrance, morphological adjustments of channel and vegetation succession.…”
Section: Discussionmentioning
confidence: 99%
“…Cutoffs are responsible for significant flow modification, changes in sinuosity and channel morphology and pattern. Eekhout and Hoitink (2015) report the lack of precise determination of chute cutoff mechanism despite extensive research in meandering river systems. Chute cutoff is defined as a new channel formation in the meander neck or inner part of the meander loop during flood events and it is a major planform control element in actively meandering rivers (Constantine et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although single‐thread streams in lowland areas often appear to be highly sinuous, they remain virtually fixed in time. Active morphological processes such as the development of alternate bars and chute cut‐off may occur as a response to human measures (Eekhout & Hoitink, ; Eekhout, Hoitink, & Mosselman, ), but after an initial period of adjustment, the streams tend to maintain stable (Eekhout, Fraaije, & Hoitink, ). Eekhout, Hoitink, de Brouwer, and Verdonschot () showed that typical deteriorated lowland streams have cross‐sectional‐averaged flow velocities of 0.08–0.13 m/s and homogeneous bed substrate.…”
Section: Introductionmentioning
confidence: 99%